Free amino acids in the digestive system of Antarctic krill, Euphausia superba, sampled in January, March and May - Heyen, Simone; Töpker, Verena; Kopke, Bernd; Cakić, Nevenka; Hüppe, Lukas; Meyer, Bettina; Wilkes, Heinz
Antarctic krill, Euphausia superba, is a key species in the Southern Ocean with an immense biomass. Ongoing climate change affects their food availability, habitat and survivability. Therefore, markers documenting changes in this species are important to monitor and discover future issues, also because krill-derived products are manufactured for human consumption. Several studies have focused on the composition of krill-derived lipids. However, they may be a potential in other metabolites to serve as tracers identifying shifts in the Antarctic environment. Krill was caught with a continuous krill pumping system in May of 2021 in the Bransfield Strait and in January and March of 2022 at the South Orkney Islands aboard the commercial krill fishing vessel Antarctic Endurance. The stomach, digestive gland and hind gut were dissected and analysed individually. Samples were initially extracted by bead-beating, with individual subsequent extraction steps adjusted for the different metabolic classes. Free amino acids from the digestive system of Antarctic krill, Euphausia superba, were measured in derivatised bead-beater extracts. Measurement of methoxycarbonyl esters was performed with gas chromatography - mass spectrometry. Identification of amino acids was based on standards.